KINERJA HOTEL THE PATRA BALI RESORT & VILLAS DENGAN PENDEKATAN BALANCED SCORECARD (BSC) - Putu Gde Himawan Saputra; I Putu Santika (Journal of Applied Management Studies, 2021)
This study aims to analyze the performance of The Patra Bali Resort & Villas Hotel with the Balanced Scorecard approach. The population in this case is the customers and employees of The Patra Bali Resort & Villas Hotel. The sample in this study was divided into two samples, namely a sample of 50 customers and a sample of 80 employees. The research on the performance of The Patra Bali Resort & Villas Hotel with the Balanced Scorecard approach will review four perspectives, namely the financial perspective, the customer perspective, the internal business process perspective and the growth and learning perspective. The results of this study found that. 1) The performance of The Patra Bali Resort & Villas based on a financial perspective shows a fairly good performance. 2) The performance of The Patra Bali Resort & Villas Hotel based on the perspective of service users shows a very good predicate performance. 3) The performance of The Patra Bali Resort & Villas based on an internal business perspective shows a fairly good performance. 4) The performance of The Patra Bali Resort & Villas based on the learning and growth perspective shows a good performance.